DAMPAK MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN KONSEP PECAHAN PENJUMLAHAN PADA SISWA KELAS 4 SD - Oktha Hardi Prawira; Rayi Siti Fitriani; Ety Sukaetini (STKIP Subang, 2026)
This study aims to determine the impact of the Problem Based Learning (PBL) model on understanding the concept of fraction addition in fourth-grade elementary school students. This research uses a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design). The research sample consisted of 28 students in the experimental class and 25 students in the control class, selected using purposive sampling technique. Data collection was carried out through pretest and posttest in the form of description questions that had been tested for validity and reliability. Data analysis techniques used descriptive statistics, normality test, homogeneity test, Mann-Whitney U test, N-Gain test, and effect size test. The results showed that there was no significant difference in the initial ability to understand the concept of fractions between the experimental class and the control class (p-value 0.594). After the intervention, the Mann-Whitney U test (posttest) showed a significance of 0.294 (sig 0.05). The N-Gain analysis recorded an increase in the experimental class of 30.04% (medium category), superior to the control class of 22.83% (low category), with the effectiveness of the treatment classified as medium category (effect size 0.205). The conclusion of this study indicates that the Problem Based Learning (PBL) model can improve students' understanding of the concept of fractions, although the effect is in the medium category. Thus, the PBL model can be used as an effective alternative to improve elementary school students' understanding of fraction concepts.